258 MANAGEMENT OF OESOPHAGO-GASTRIC LEAKS FOLLOWING MINIMALLY INVASIVE IVOR LEWIS OESOPHAGO-GASTRECTOMY USING DOUBLE PIGTAIL STENTS. (17th September 2021) - Tan, Jeremy; Wong, Wai Keong; Yeung, Baldwin; Toh, Bin Chet; Ong, Lester; Lim, Chin Hong; Lim, Eugene; Eng, Alvin; Ong, Hock Soo; Lee, Zhen Jin; Lye, Tiffany; Chan, Weng Hoong
Abstract:  : Anastomotic leak following Ivor Lewis oesophago-gastrectomy is a major complication with high morbidity and mortality. We report our experience with three such cases where endoscopically deployed double pigtail stents (DPT) were used to help manage the leaks. Methods: Three patients from October 1, 2019 to February 29, 2020 experienced leakage from the oesophago-gastric anastomosis following minimally invasive Ivor Lewis oesophago-gastrectomy. These occurred on post-operative day 9, day 29 and day 7 respectively. All cases were managed with endoscopic deployment of double pigtail stents along with other adjunctive measures. Results: To date all patients remain alive, with sepsis under control. One of the patients had been able to have his double pigtail stent removed at six weeks and he has been able to commence adjuvant chemotherapy. Another patient had a follow-up contrast study one week after DPT insertion which showed no further contrast extravasation and was able to recommence oral intake. The third patient has a left empyema (managed conservatively with a combination of internal DPT and external pigtail drainage) which is gradually resolving. Conclusion: Endoscopically deployed DPTs are a useful tool in the armamentarium for managing oesophago-gastric anastomotic leaks in selected patients following Ivor Lewis oesophago-gastrectomy. They are advantageous in that stent migration does not appear to be an issue, nor is there any problem with leakage around the stent. Patients are mostly able to restart oral intake soon after insertion of DPTs. This reduces the morbidity associated with these anastomotic leaks, and reduces the number of interventions needed.